Analisis Study Kasus Persalinan Patologis Pada Ny. J Umur 40 Tahun G4P2A1 Dengan Persalinan Spontan Atas Indikasi Ketuban Pecah Dini (KPD) Di RSUD Brebes - Ahmad Ridlo; Himatul Khoeroh (PPNI UNIMMAN, 2024)
Premature Rupture of Membranes (PROM) is a condition where the amniotic membranes rupture before signs of labor appear. Cases of premature rupture of membranes at Brebes District Hospital are cases that are often encountered; this case reached 273. The impact of PROM has a high risk to the continued health of the mother and fetus. The aim of this research is to analyze midwifery care comprehensively using Varney's 7 steps. This research uses a qualitative descriptive method with a case study approach. Data collection used interview methods, observation, physical examinations, supporting examinations, medical records, KIA books, and other literature. The main informant was Mrs. “J”, while the additional informants were the coordinating midwife, general practitioner, obstetrician, laboratory officer, husband, and family. Based on the results, Mrs. “J” experienced problems during labor with premature rupture of membranes. Based on the results, Mrs. “J” at the time of childbirth had problems with the cranium being broken prematurely after anamnesies and continuous examination by midwife by conducting an in-depth examination with thin portio results, opening 10 cm, UUK point, cranial membrane (-), presentation of the head, and head-down hodge IV. The baby is born spontaneously, with strong crying and normal reflexes